Is healthy food affordable in Rajshahi, Bangladesh? Cost and affordability of a healthy diet - Chauhan, Alka; Tomar, Anindya; Headey, Derek D.; Scott, Samuel P.; Kishore, Avinash; Menon, Purnima (CGIAR System Organization, 2024)
The Transforming Agrifood Systems in South Asia (TAFSSA) local food systems assessment aims to provide a reliable, accessible and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It was designed to be a district-level multi-year assessment. Using data collected in February–March 2023, this data note describes household spending behavior on foods, share of food groups in cost of healthy diet, and how much money households have to spend to achieve a healthy diet. This is one of a set of data notes that, together, provide a holistic picture of the agrifood system in the district.